‎Nonlinear Contraction Mappings in b-metric Space and Related Fixed Point Results with Application - Muhammed Raji; Arvind Kumar Rajpoot; Laxmi Rathour; Lakshmi Narayan Mishra; Vishnu Narayan Mishra (Transactions on Fuzzy Sets and Systems)
The paper aims to introduce some fixed point results in the setting of sequential compact b-metric spaces to prove Eldeisten-Suzuki-type contraction for self-mappings‎. ‎These contributions extend the existing literature on fixed point for ordered metric spaces and fixed point theory‎. ‎Through illustrative examples‎, ‎we showcase the practical applicability of our proposed notions and results‎, ‎demonstrating their effectiveness in real-world scenarios‎.